Accounts Receivable Information System at PT. Latinusa, Tbk - Tri Wahyudi; Kurniasih Dwi Astuti; Intan Putri Kinasih (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this research is to determine the suitability of accounts receivable accounting information at PT. Latinusa Tbk. The method used in writing this final assignment is descriptive method. This writing uses primary data and secondary data obtained from PT. Latinusa Tbk. Data sources come from field studies and literature. How to collect data through observation, interviews and documentation collected from PT. Latinusa Tbk. Based on the results of industry internships obtained in the field, account receivable accounting information system at PT. Latinusa Tbk, is in accordance with the theory.